Minimum Wage and Tolerance for High Incomes - Andrea Fazio; Tommaso G. Reggiani (Institute of Labor Economics (IZA), 2023)
We suggest that stabilizing the baseline income can make low-wage workers more tolerant towards high income earners. We present evidence of this attitude in the UK by exploiting the introduction of the National Minimum Wage (NMW), which institutionally sets a baseline pay reducing the risk of income losses and providing a clear reference point for British workers at the lower end of the income distribution. Based on data from the British Household Panel Survey (BHPS), we show that workers who benefited from the NMW program became relatively more tolerant of high incomes and more likely to support and vote for the Conservative Party. As far as tolerance for high incomes is related to tolerance of inequality, our results may suggest that people advocate for equality also because they fear income losses below a given reference point.
Keywords: H10; H53; D63; D69; Z1; 330; reference point; loss aversion; minimum wage; redistribution; inequality; UK